Cumulative Human Impacts on Pinnipeds Over the Last 7,500 Years in Southern South America - Nye, Jonathan W. (2018)
Our research program on this topic combines zooarchaeological and stable isotope studies from a historical ecology perspective. We originated this approach, and developed new analytical techniques, to better link archaeological evidence with paleo-ecosystem reconstructions (Zangrando, Panarello et al. 2014). In order to assess the relationship between pinnipeds and hunter-gatherers in Tierra del Fuego, we developed zooarchaeological analyses based on predictions from foraging models. Since information about past abundance or distribution of prey is rare in the southern South Atlantic, zooarchaeological evaluations were basedmainly on modern ecological parameters. Current foraging ecology of pinnipeds may be a useful framework for understanding archaeological evidence; however, that framework might present an incomplete picture of the actual range ofbehaviors and ecological roles that these resources could have provided for human populations in the past. In fact, the historical distribution of pinnipeds in Patagonia and Tierra del Fuego is poorly understood. Moreover, species distributions are likely to have fluctuated throughout time because of different environmental factors, or as a by-product of cumulative human impacts on marine ecosystems. Thus, the range of variation reflected in our knowledge about current pinniped distribution may not sufficiently represent the past.Against this context, an isotopic zooarchaeological approach provides a convenient route to expand our knowledge about human-pinniped relations at long-time scales (Zangrando,Panarello et al. 2014).